Evaluating Alternative Work-Integrated Learning Opportunities: Student Perceptions of Interdisciplinary Industry-Based Projects - Hayes, Melanie; Cejnar, Leela (Journal of University Teaching and Learning Practice, 2020)
Industry and Community Project Units (ICPU) are a work-integrated learning (WIL) initiative designed to provide an interdisciplinary, project-based experience for students based on real-world industry problems. With any new program, reflecting on the course delivery is essential for future quality improvement. Brookfield (2017) has suggested many student-centred approaches through which we can reflect on teaching practice, including Letters to Successors, whereby current students reflect on their experience and provide guidance for surviving and thriving the course, in a letter to future students. This study aimed to analyse the anonymous Letters to Successors penned by four separate ICPU cohorts, to understand students’ perceptions of undertaking interdisciplinary, industry-based projects. The text within the Letters to Successors was analysed adopting a thematic analysis, using a realist and inductive approach. Four key themes were identified in the letters: working with others, focusing on tasks, having fun, and the unique experience. The students were overwhelmingly positive in describing their experience and were grateful for the opportunity to participate in a unit unlike others in their degree programs. Many of the skills and behaviours the students attributed to success align with the transferable skills required to develop their employability; this demonstrates the value of this non-placement WIL initiative as an alternative for traditionally lengthy placements or internships that can be burdensome for both student and industry. Further research to expand our findings, or to alternatively explore the views of staff and industry partners, would be valuable in ongoing evaluations of interdisciplinary, industry-based projects as an alternative model of WIL.